Mache Papanicolaou (1890–1982), the dedicated companion of the great benefactor: An interview with Dr Julie Kokkori, one of the only living relatives of Dr George N. Papanicolaou - Mammas, Ioannis N. (Exp Ther Med, 2019)
Mache Papanicolaou (Volos, Greece, 1890 - Miami, Florida, USA, 1982) was the soul of absolute dedication to research, science and humanity of her lifelong partner, Dr George N. Papanicolaou (Kymi, Greece, 1883 - Miami Florida, USA, 1962). Her devotion to him, her endless support during their first years in the USA, as well as during the period before the approval of the Pap smear test and her selfless contribution to this revolutionary work were invaluable, indeed. In this article, which is dedicated to the memory of Mache Papanicolaou, we have the great honour to host the testimony of one of the only living relatives of Dr George N. Papanicolaou. Dr Julie Kokkori is the granddaughter of Nasos N. Papanicolaou (Kymi, Greece, 1880-Athens, Greece, 1958), the oldest brother of Dr George N. Papanicolaou, and daughter of the niece of Dr George N. Papanicolaou, Maria Kokkori (Trikala, Greece, 1918 - Athens, Greece, 2012), author of the first book in the Hellenic literature on the life of Dr George N. Papanicolaou entitled ‘George N. Papanicolaou: through his life and work’.